Na2MoO2−δF4+δ – a perovskite with a unique combination of atomic orderings and octahedral tilts. Issue 84 (9th September 2015) - Ishikawa, Hajime; Munaò, Irene; Bode, Bela E.; Hiroi, Zenji; Lightfoot, Philip
Abstract : Na2 MoO2− δ F4+ δ represents the first example of a perovskite exhibiting simultaneous A-site, B-site and anion site order, together with a complex tilt system. Abstract : Na2 MoO2− δ F4+ δ ( δ ∼ 0.08) displays a unique variant of the perovskite structure, with simultaneous (Na, vacancy) ordering on the A-site, (Na, Mo) ordering on the B-site, (O, F) ordering on the anion site and an unusual NaNbO3 -like octahedral tilt system.